Uji Viabilitas dan Vigor Benih Telang(Clitoria ternatea) dari Berbagai Lokasi Tumbuh - Mardiana Lukman; Sri Soenarsih DAS; Rima Melati (Universitas Khairun, 2021)
The flower of Telang usually grows in the yard or the edge of the forest. This plant typically is a gourd plant. Its seed is classified as orthodox seed, meaning that its seed naturally can be characterized as dried without being damaged. This study aimed to determine the viability and vigor of the Telang seeds (Clitoria ternatea L). A Completely Randomized Design (CRD) consisted of 6 treatments based on seed origin: South Ternate, North Ternate, Tidore, Thailand, Subaim, and Central Ternate. The experiment was repeated four times, so it consisted of 24 units. The observation variables consisted of growth potential, germination capacity, the vigor of sprouts, growth speed, synchronous growth, and dead seeds. We performed an Analysis of Variance (ANOVA) to analyze the data. The results showed that the origin of seeds had a significant effect on growth potential, germination, sprout vigor, growth speed, synchronous growth, and dead seed. The best seed viability and vigor were found in North Ternate seeds.